Six Thinking Hats Strategy and its Role in Building the Educational Research Problem - ghediri, Maroua; ckahhoul, shafika (Journal of Social Sciences and Humanities, 2021)
This research paper dealt with the six-hats of thinking and its role in building the problem of educational research on the theoretical side, by focusing on the terms of its formulation and the most important sources, then the six hats and their purpose, and providing a small model on how to build a research problem in the way of the six hats of thought. The study concluded that the investment of the six hats improves the way of thinking and promoting them from randomness to organization in thinking.